Aprendizagem maker e ensino de engenharia - Silva, José Nilton da (2020)
With the constant transformations and great speeds in the field of technology, the unforeseen events that occur in industry, logistics and the environment request professionals with skills in creativity and innovation. Collaborative work has been shown to be increasingly present in corporations and educational institutions in the country and abroad. The present work has the main objective of verifying the perception of professors of the Production Engineering course of a private institution of higher education in the city of São Paulo about maker learning, considering the current challenges of industry 4.0: presenting a contextualized, reflective and technically prepared in an environment of unforeseen and uncertainties. Thus, initially, some considerations about the maker culture are outlined, as well as about the need for the formation of a new professional model in engineering, allowing to articulate the expectations of university education with those of the labor market. Through this research, we sought to reflect on the methodologies used by teachers during their classes. The final objective of the research is to devise a proposal that encourages the participant's active and reflective participation. In this way, it is possible to interconnect Maker learning, in the concept of Cris Anderson, with considerations on teaching engineering from the perspective of adult education based on the works of Jean-Marie Barbier. The research involved data collection, encouraging the need to apply a questionnaire to professors at the Faculty of Engineering. Thus enabling the formulation of a categorical analysis by the method of Pierre Bardin, based on data collections. The results conditioned in this work, lead to a perspective of continuous improvement, based on the active methodology of the maker culture, for the preparation of educational agents for a better use of new technologies for didactic- pedagogical improvement, which will bring not only an improvement in professional training, but also in the training of innovative and reflective human beings.